In situ characterization of phase transformation and reactivity of high surface area lanthanum-based Ru catalysts for the combined reforming of methane - Faroldi, Betina María Cecilia (2013)
A lanthanum oxycarbonate phase (La2O2CO3) with high surface area was prepared as support of Ru catalysts. The metal was added by wet impregnation or incorporated during the oxycarbonate synthesis. The reactivity of the lanthanum and ruthenium species was studied through in situ Raman under dry reforming of methane conditions with and without oxygen addition. When Ru was incorporated by wet impregnation, the solid showed a higher reactivity of lanthanum oxycarbonate to the formation of La2O3 in a hydrogen flow even at low temperatures while RuOx was completely reduced at 400 °C. It was also found that the reduced ruthenium species could be re-oxidized by CO2 at the reaction temperature (550 °C). Under the dry reforming of methane, the metallic Ru did not change its oxidation state and the formation of graphitic carbon and oxycarbonate was observed. With the addition of oxygen, the same phase transformation occurred as in the case of the dry reforming of methane. However, the re-oxidation of Ru0 species was observed through in situ Laser Raman spectroscopy and pseudo in situ XPS measurements. These measurements allowed us to advance in the understanding of the solid transformations produced during methane reforming reactions.